2019
DOI: 10.1093/cdn/nzz029.p02-001-19
|View full text |Cite
|
Sign up to set email alerts
|

Digit Variability in Carotenoid Scores Obtained with the Veggie Meter: A Pilot Study (P02-001-19)

Abstract: Objectives To determine which digit and hand have the highest and lowest skin carotenoid scores, to compare inter-and-intra-hand variability of digits, and to determine if results are consistent with another subject. Methods Two subjects’ first(F1), second(F2), third(F3) and fifth(F5) digits on both hands were measured for skin carotenoids with a Veggie Meter, for 3 times on each of 18 days over a 37-day period. Data were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When assessing skin carotenoid levels, we did not scan the same hand (dominant or nondominant), which may have affected the reliability of measurements. VM scores have been shown to vary by hand and digit [ 62 ]. In longitudinal studies of this type, investigators assessing skin carotenoids with the VM are therefore encouraged to scan the same finger at each assessment.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing skin carotenoid levels, we did not scan the same hand (dominant or nondominant), which may have affected the reliability of measurements. VM scores have been shown to vary by hand and digit [ 62 ]. In longitudinal studies of this type, investigators assessing skin carotenoids with the VM are therefore encouraged to scan the same finger at each assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was planned prior to standardization, and we measured the middle finger of the left hand. There has been no consensus about the difference in VM scores in different fingers [ 49 ], but our preliminary study found no difference among the eight fingers of both hands (except little fingers, unpublished data). Fifth, VM scores were verified in the US population by dietary assessment [ 35 ], but not in the Japanese population.…”
Section: Discussionmentioning
confidence: 60%
“…The dominant hand index finger was used with all participants during the Fall 2018 and Spring 2019 timepoints. Subsequent to this timepoint, an international meeting of Veggie Meter ® researchers convened and it was determined that the non-dominant ring finger should be used [42], and in Fall 2019 the non-dominant ring finger was used instead of the dominant hand index finger.…”
Section: Resultsmentioning
confidence: 99%
“…At the first data collection time points, students were not asked to clean their hands prior to measurements and the index finger on the dominant hand was used. After the publication of more research using the Veggie Meter ® , the protocol evolved to include hand cleaning and the use of the non-dominant ring finger [42]. Since completion of this study, users of the Veggie Meter ® worked together to create a comprehensive set of recommendations for use in different research settings [53].…”
Section: Discussionmentioning
confidence: 99%